Alzheimer's “Prevention” vs. “Risk Reduction”: Transcending Semantics for Clinical Practice - Hodes, John F.; Oakley, Carlee I.; O'Keefe, James H.; Lu, Peilin; Galvin, James E.; Saif, Nabeel; Bellara, Sonia; Rahman, Aneela; Kaufman, Yakir; Hristov, Hollie; Rajji, Tarek K.; Fosnacht Morgan, Anne Marie; et al. (Frontiers in Neurology, 2019)
The terms “prevention” and “risk reduction” are often used interchangeably in medicine. There is considerable debate, however, over the use of these terms in describing interventions that aim to preserve cognitive health and/or delay disease progression of Alzheimer’s disease (AD) for patients seeking clinical care. Furthermore, it is important to distinguish between Alzheimer’s disease prevention and Alzheimer’s dementia prevention when using these terms. While prior studies have codified research-based criteria for the progressive stages of AD, there are no clear clinical consensus criteria to guide the use of these terms for physicians in practice. A clear understanding of the implications of each term will help guide clinical practice and clinical research. The authors explore the semantics and appropriate use of the terms “prevention” and “risk reduction” as they relate to AD in clinical practice.